Gandari Menjelaga Pertunjukan Drama Tari Wayang Kontemporer - Anggraeni, Anggraeni (Pascasarjana ISBI Bandung, 2019)
Gandari Menjelaga is a dance drama taken from wayang story, that is Epos Mahabarata. This is a dance composition telling about a female character named Gandari, the daughter of King Prabu Subala of Gandaras Kingdom. She should sacrifice her beauty by covering her eyes with white cloth as her loyalty to her fate. The concept of this work describes a self-denial of a woman toward her life. The combination of traditional and contemporary dance becomes the main element in producing the dance drama. The dramatic structure is arranged into four scenes whose settings are in the Gandara Kingdom Gate, in Gandara Palace, and in Dewi Gandaris Courtyard. This dance drama is accompanied by gamelan compositionKeywords: Dance Drama, Gandari Menjelaga, Wayang Dance